Influence of clinical factors on the protective or deleterious impact of genetic variants in orthodontically induced external root resorption: an observational study - Henriqueta Coimbra Silva; Nuno Lavado; Filomena Canova; Miguel Guevara Lopez; Fernando J. Regateiro; Sónia A. Pereira (BMC, 2022)
Abstract Background Prediction of susceptibility to Orthodontically Induced External Apical Root Resorption (OIEARR) has been hampered by the complex architecture of this multifactorial phenotype. The aim of this study was to analyze the impact of the interaction of multiple variables in the susceptibility to OIEARR. Methods The study evaluated 195 patients requiring orthodontic treatment. Nine clinical and treatment variables, single nucleotide polymorphisms (SNPs) from five genes and variables interactions were analyzed as risk factors for OIEARR using a multiple linear regression model. Results The model explained 29% of OIEARR variability (ANOVA: p < 0.01). Duration of treatment was the most important predictor and gender was the second, closely followed by premolar extraction. For genes encoding osteoprotegerin (OPG), the receptor activator of nuclear factor κ B (RANK) and the IL1 receptor antagonist (IL1RN), the effect of analyzed variants changed from protective to deleterious depending on the duration of treatment and the age of the patient. Conclusions This work shows that in OIEARR the impact of genetic susceptibility factors is dynamic changing according to clinical variables.